Respuesta :

Answer:

It is D, just got it correct on edge.

The inverse of the given function are x = 3 f(x) - 6 , x = 3 h(x) - 6 , x = 3h(x) +6 , x = h(x)/3 +2/3 and x = h(x)/3 + 2.

What is an inverse function?

An inverse function is a function where dependent and independent variables interchange.

For example, if we have a function y = x + 3 then their y will be independent and x is dependent.

If we change it by x = y -3 where x will be independent and y will be dependent.

In the first given function

f(x) = x/3 + 2 now

x = 3 f(x) -6 will be first inverse function.

In the second given function

h(x) = x/3 +2 now

x = 3 h(x) - 6  will be inverse.

In the third given function

h(x) = x/3 -2 now

x = 3 h(x) + 6 will be inverse.

In the fourth given function

h(x) = 3c -2 now

x = h(x)/3 +2/3 will be inverse.

In the fifth given function

h(x) = 3x - 6 now

x = h(x)/3 +2 will be inverse.

For more about inverse function

https://brainly.com/question/12524559

#SPJ5